Chemistry of riming: the retention of organic and inorganic atmospheric trace constituents - A. Jost; A. Jost; M. Szakáll; K. Diehl; S. K. Mitra; S. Borrmann; S. Borrmann (Atmospheric Chemistry and Physics, 2017)
During free fall in clouds, ice hydrometeors such as snowflakes and ice particles grow effectively by riming, i.e., the accretion of supercooled droplets. Volatile atmospheric trace constituents dissolved in the supercooled droplets may remain in ice during freezing or may be released back to the gas phase. This process is quantified by retention coefficients. Once in the ice phase the trace constituents may be vertically redistributed by scavenging and subsequent precipitation or by evaporation of these ice hydrometeors at high altitudes. Retention coefficients of the most dominant carboxylic acids and aldehydes found in cloud water were investigated in the Mainz vertical wind tunnel under dry-growth (surface temperature less than 0 °C) riming conditions which are typically prevailing in the mixed-phase zone of convective clouds (i.e., temperatures from −16 to −7 °C and a liquid water content (LWC) of 0. 9 ± 0. 2 g m−3). The mean retention coefficients of formic and acetic acids are found to be 0. 68 ± 0. 09 and 0. 63 ± 0. 19. Oxalic and malonic acids as well as formaldehyde show mean retention coefficients of 0. 97 ± 0. 06, 0. 98 ± 0. 08, and 0. 97 ± 0. 11, respectively. Application of a semi-empirical model on the present and earlier wind tunnel measurements reveals that retention coefficients can be well interpreted by the effective Henry's law constant accounting for solubility and dissociation. A parameterization for the retention coefficients has been derived for substances whose aqueous-phase kinetics are fast compared to mass transport timescales. For other cases, the semi-empirical model in combination with a kinetic approach is suited to determine the retention coefficients. These may be implemented in high-resolution cloud models.